The Role of PMII Suromenggolo Rayon in Strengthening The Islamic Character of The Wates Village Community Through The Sahasra Magandi Program - Munawwirulloh, Hanif; Dwijayanto, Arik; Wathoni, Syamsul (IAIN PONOROGO, 2025)
This study analyzes the role of PMII Rayon Suromenggolo in strengthening the Islamic Character of the Wates Village community through the Sahasra Magandi program (2019–2024). Using a longitudinal qualitative approach (in-depth interviews with 10 PMII cadres and document analysis), three main strategies were found: (1) A cultural approach through the integration of Islamic values with local traditions (e.g., transforming the slametan ritual into a means of productive alms); (2) Moderate Islamic education based on the Aswaja principles (tawasuth, tawāzun, tasāmuh, and I'tidāl) in TPQ/SD; (3) Collaboration between religious and community leaders as theological legitimacy and institutionalization of the program. Analysis based on the theory of Prophetic Islam (Kuntowijoyo) and character education (Lickona) shows that this program successfully internalized the value of moderation through moral action, while simultaneously addressing the challenges of moral degradation and poverty. Key findings: Cultural-institutional synergy catalyzes the contextual transformation of Islamic Character, with implications for a village empowerment model based on student organizations.